2012
DOI: 10.2460/javma.240.12.1488
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for colic in equids hospitalized for ocular disease

Abstract: There was a high incidence of colic in equids hospitalized with ocular disease in this study. Findings from this study may help identify equids at risk for development of colic and thereby help direct implementation of prophylactic measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 32 publications
2
21
1
1
Order By: Relevance
“…Multiple studies have reported specific morbidity rates for PAC and myopathy/neuropathy ; however, the authors are aware of only one study reporting the overall morbidity rate , which was comparable (13.7%) to the present study.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Multiple studies have reported specific morbidity rates for PAC and myopathy/neuropathy ; however, the authors are aware of only one study reporting the overall morbidity rate , which was comparable (13.7%) to the present study.…”
Section: Discussionsupporting
confidence: 60%
“…A multicentre survey in the United States and Canada over a 31 year period reported only 30 cases of post anaesthetic myelomalacia [16], and only 2 cases of myelomalacia in a TB have been reported in the literature [16,17]. Multiple studies have reported specific morbidity rates for PAC [4][5][6][7][8] and myopathy/neuropathy [13,18]; however, the authors are aware of only one study reporting the overall morbidity rate [3], which was comparable (13.7%) to the present study.…”
Section: Discussionsupporting
confidence: 55%
“…Several surgical techniques have been reported in donkeys for corneal ulcers resolution, such as the use of a porcine urinary bladder extracellular matrix graft in a miniature donkey with severe unilateral keratomalacia [119]. When medically treating donkeys with corneal ulcers and, if atropine is administered, gut motility, fecal production, and heart rate should be closely monitored [120]. Nonulcerative keratitis (e.g., eosinophilic keratitis) has been reported both in mules and donkeys.…”
Section: Ophthalmologymentioning
confidence: 99%
“…L.A. Patipa and colleagues from the University of Georgia, USA, have published the results of a study to evaluate the incidence of colic and the risk factors for colic in equids hospitalised for ocular disease ( Patipa et al. 2012 ).…”
Section: Risk Factors For Colic In Hospitalised Horsesmentioning
confidence: 99%